Determinan Of Skin Disease In Scavengers - Melva Saragih; David Siagian (TOUR HEALTH JOURNAL, 2022)
Background: Skin  disease  is  a  skin  disorder  with  symptoms  of itching  and  is  characterized objectively  by  patches,  rashes,  or inflammation.     Skin     diseases     are     often     experienced     by scavengers. Purpose: The   purpose   of   this   study   wasto   determine   the factors   associated   with   the   incidence   of    skin   disease   in scavengers in garbage dumps. Method: This  study  is  an  observational  analytic  study  with  a cross-sectional  study  design  from  January  to  August  2021.  The population  is  scavengers  who  scavenge  around the garbage dumpsat Medan  Polonia.Data  analysis  methodsusing  Chi-square with a significance level of 0.05. Result: The  results  of  this  study  are  that  there  is  a  relationship between  personal  hygiene  (0.05)  and  a  history  of  skin  disease (0.03)  with  the  incidence  of  skin  disease  in  scavengers  around the garbage    dumpsat Medan    Polonia,    and    there    isno relationship  between  personal  protective  equipment  and  skin disease incidence in scavengers in around the garbage dumpsat Medan Polonia. Conclusion: It  is  hoped  that  related  agencies  such  as  Public health  center  at  Medan  Polonia,  are  expected  to  be able  to empower  scavengers  and  educate  scavengers  to  be  better  able to  maintain  and  maintain  personal  health  in  order  to  avoid health  problems  in  this  case,  especially  diseases  caused  by  the work environment.